2009
DOI: 10.3177/jnsv.55.186
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Levels in Lung Tissue of Rats with Bleomycin Induced Pulmonary Fibrosis

Abstract: Summary Bleomycin (BLM) is a chemotherapeutic agent against different carcinomas, one dose of which causes dependent pulmonary fibrosis. The present study was taken up in order to measure the retinyl ester, ␣ -tocopherol and cholecalciferol (vitamin D 3 ) level in lung tissue in the rats following BLM-induced fibrosis. Fourteen rats were randomly divided into two groups as a control and a BLM group. On the day of the experiment, the BLM group rats were instilled with BLM (7.5 mg/kg) and the control group with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…They concluded that ATRA improved the fibrosis induced by BLM in the lung tissues of rats; their data may provide a basis to explore the clinical use of ATRA in order to prevent fibrosis induced by pathologic radiation of the lung implying pulmonary fibrosis. Mert et al (2009) reported that there was a decrease in the retinyl ester level in the pulmonary fibrosis lung tissue, produced by giving bleomycin to rats. There was a decrease in the retinol level for all groups addressed in study (p>0.05) as seen in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that ATRA improved the fibrosis induced by BLM in the lung tissues of rats; their data may provide a basis to explore the clinical use of ATRA in order to prevent fibrosis induced by pathologic radiation of the lung implying pulmonary fibrosis. Mert et al (2009) reported that there was a decrease in the retinyl ester level in the pulmonary fibrosis lung tissue, produced by giving bleomycin to rats. There was a decrease in the retinol level for all groups addressed in study (p>0.05) as seen in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These effects include reduced risk of many forms of cancer , bacterial infections (Bikle 2008), viral infections (Cannell 2006), autoimmune diseases (Munger et al, 2006), and cardiovascular disease . Mert et al (2009) reported that there was a significant decrease in the vitamin D3 level in the pulmonary fibrosis lung tissue, produced by giving rats bleomycin (p<0.001). For this study, while there was only an increase in the vitamin D levels of the BLM group, decreases were observed in all other groups (p>0.05) as shown in Table 1.…”
Section: Blm: Bleomycinmentioning
confidence: 99%
“…In the laboratory, 25-hydroxyvitamin D 3 levels are reduced in rats with bleomycin-induced lung fi brosis. 42 Further, vitamin D appears to inhibit the profi brotic effects of transforming growth factor b in lung fi broblasts and epithelial cells, and may blunt epithelial-to-mesenchymal tran sition. 43 The specifi c mechanisms for autoimmune parenchymal lung injury and how tissue vitamin D levels modulate its occurrence need to be further investigated.…”
Section: Adjusted Modelsmentioning
confidence: 99%
“…In fact, studies have suggested that vitamin D may be involved in IPF 17,18,29 . However, the effects of vitamin D on pulmonary fibrosis have not previously been explored, despite in vitro evidence supporting its efficacy 24 30 31 . To the best of our knowledge, we are the first to demonstrate that vitamin D treatment attenuated pulmonary fibrosis induced by bleomycin in mice, suggesting that vitamin D may be potentially used in IPF treatment in human patients.…”
Section: Discussionmentioning
confidence: 99%